2022
DOI: 10.1212/wnl.0000000000200701
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mental Activity, Disease Susceptibility, and Risk of Dementia

Abstract: Background and objectivesThe association between patterns of physical/mental activity and dementia and how it is affected by disease susceptibility remains unknown. We aimed to examine the association between patterns of physical and mental activity and dementia, and whether it can be modified by disease susceptibility to dementia.MethodsIn a prospective cohort study based on UK Biobank, 501,376 dementia-free participants were recruited in 2006-2010 and followed from one year after the recruitment date until t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…Previous clinical and basic studies have shown that suffering from metabolic disorders such as diabetes and obesity may be involved in the development of dementia [6,[33][34][35]. Our findings support the existence of a relationship between anthropometric composition and an excess of body fat with cognitive preservation in cognitively healthy people over 60 years of age.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous clinical and basic studies have shown that suffering from metabolic disorders such as diabetes and obesity may be involved in the development of dementia [6,[33][34][35]. Our findings support the existence of a relationship between anthropometric composition and an excess of body fat with cognitive preservation in cognitively healthy people over 60 years of age.…”
Section: Discussionsupporting
confidence: 87%
“…This fact could be also explained due to the visible deficit in muscle mass in the group with lower cognitive score. In any case, physical activity has been shown to be a great tool in preserving cognitive status and preventing dementia [35,47].…”
Section: Discussionmentioning
confidence: 99%
“…The present study included demographic characteristics (age, sex [male or female]), sociodemographic characteristics (education [college/university or below college], income [< 18,000 or 18,000-52,000 or ≥ 52,000 £/year] [18], race [white or others], Townsend index), lifestyle factors (smoking status [never or current or former], alcohol consumption [0 or 0.1-30 or ≥ 30 g/day] [19,20], diet quality score [see Additional file 3], sedentary behavior [hours/day] and MVPA [MET-minutes/week]), body mass index (BMI, kg/m 2 ) and family history of CVD (yes or no) as covariates according to previous studies on similar topic [5,7,17]. Missing indicator approach was used in the regression model by coding missingness as a dummy variable.…”
Section: Covariatesmentioning
confidence: 99%
“…Prospective studies of older adults have shown that cardiovascular fitness is associated with both increased grey and white matter volume 41 and white matter integrity, 42 suggesting a neuroprotective effect of physical activity. 43 Alternatively, the damaged white matter may lead to reduced physical activity via impaired mobility, gait or balance dysfunction as well as reduced cognitive ability, suggesting reverse causality. 44 , 45 Accounting for such reverse causality by additionally controlling for concurrent neurodegeneration and cognitive impairment did not substantially impact our findings.…”
Section: Discussionmentioning
confidence: 99%